СОСТОЯНИЕ АТОМОВ ЖЕЛЕЗА В ВЫСОКИХ ВЕЗУВИАНАХ ПО ДАННЫМ МЁССБАУЭРОВСКОЙ СПЕКТРОСКОПИИ - Русаков В.С.; Ковальчук Р.В.; Боровикова Е.Ю.; Куражковская В.С. (My University, 2006)
The vcsuvianitc sample collection with wide chemical composition variations were investigated by Mossbaucr spectroscopy methods. Experimental Mossbaucr spectra generally consist of five quadrupole doublets. Hyperfme parameters of three and two of them correspond to Fc*+ and Fe3< ions, accordingly. The analysis and comparison of the received parameters with vesuvianite structure and literature data allowed us to find ferrous and ferric iron distribution into crystallographically noncquivalcnt structural sites. It was shown that in vcsuvianitc samples with low Mg atom and high Al atom contents a significant amount of iron atoms determined in five-coordinated Y(l) site in bivalent state. In vesuvianite samples with high Mg atom and low Al atom contents Fe3' ions located in octahedral Y(3) site dominate.
Keywords: 539.172:539.2:548.3